Strategies for Research Capacity Building by Family Physicians in Primary Healthcare: a Scoping Review Protocol - Gil Conde, M (2024)
Introduction: The qualities of primary healthcare (PHC) make it a very relevant environment for research; however, there is still work to be done to enhance the research capabilities of family physicians in healthcare units. Considering there is no ongoing review that specifically addresses this objective, the proposed goal of this scoping review is to determine the depth of the literature on the current strategies that support research capacity building among family physicians in the context of PHC. Methods and analysis: The scoping review will include studies from PubMed, Scopus, Web of Science, Cochrane Library and grey literature, published from 2008 to 2023, that address strategies to promote research capacity building among family physicians in the context of PHC. Only studies published in English, Portuguese or Spanish will be considered. All study designs, including quantitative, qualitative and mixed-methods studies, will be eligible for inclusion. The literature search will be performed from January to March of 2024 and data charting will employ a descriptive-analytical method, systematically summarising study objectives, methodologies, findings and implications. This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols and the review will employ the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. Ethics and dissemination: This review does not need ethical approval. Peer-reviewed publications, policy summaries, presentations at conferences and involvement with pertinent stakeholders are all part of our outreach approach.